BRIDGING COASTAL RESEARCH PROGRAM BETWEEN INDONESIA AND JAPAN - Arifin, Zainal; Saito, Hiroaki (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2019)
The JSPS Core-to-Core Research and Education Network on Coastal Ecosystems in Southeast Asia (RENSEA) 2016-2019 program has benefited Indonesian and Japanese researchers, as well as researchers in Southeast Asia. The program consists of three research groups; G1: Physical oceanography, G2: Biodiversity, and G3: Marine pollution. Considering the vast geographical area of Indonesia, managing joint research at the national level is challenging. Few active members, lack of funding, as well as the reorganization of research institutions over the last two years, pose more challenges. Funding as an engine of research execution has become highly competitive in recent years; therefore, research groups need to be more active in securing available funding at the national level, such as the COREMAP-CTI demand-driven research program, LPDP research scheme, and INSINAS research fund. From the science management perspective, the regional Core-to-Core RENSEA program needs to adapt to global trends in marine science with closer communication during the planning and execution of research projects. We recommend that joint research projects are developed to have more joint supervisory of graduate students; therefore, the collaboration would result in joint research publications and formal degrees for young scientists at the end of the program. In this way, the JSPS Core-to-Core program would have more significant benefits to the development of coastal science and research cooperation.